On the calculation of volume. II - Balle, Solvej, 1962- (Balle, Solvej, 1962- On the calculation of volume, 2024)
Book II of Solvej Balle's astounding seven-part series On the Calculation of Volume beautifully expands on the speculative premise of Book I, drawing us further into the maze of time, where space yawns open, as if suddenly gaining a new dimension, extending into ever more fined-grained textures. Within this new reality, our senses and the tactility of things grows heightened: sounds, smells, sights, objects come suddenly alive, as if the world had begun whispering to us in a new language.